Formulation Combination Of Kecombrang (Etlingera elatior) Leaf Extract And Papaya Leaves (Carica papaya L.) As Antidiabetes - Simorangkir, Delisma Marsauli; Linta Meliala; Masria Sianipar; Evi Depiana; Ella Pratiwi (Jurnal FARMASIMED (JFM), 2024)
Diabetes imellitus iis ia ichronic imetabolic idisease icharacterized iby iincreased iblood iglucose ilevels ithat ican ibe itreated iwith itraditional imedicine iderived ifrom iplants. iOne iexample iof iplants ithat ican ireduce iblood iglucose ilevels iis ikecombrang ileaves iand ipapaya ileaves iwhich icontain iflavonoids. iThe ipurpose iof ithis istudy iwas ito idetermine ithe ieffect iof icapsule iadministration iof ia icombination iof ikecombrang ileaf iextract iand ipapaya ileaf iextract iin ireducing iblood iglucose ilevels icompared iwith iglibenclamide. iThe istudy iused i24 irats iinduced iby ialloxan iand idivided iinto i8 igroups that is i icapsule ibase,i iglibenclamide idose i0.45 img/kgBB (positive icontrol), ikecombrang iextract icapsules idose i100 img/kgBB, ipapaya iextract icapsules idose i200 img/kgBB, icombination iof ikecombrang iextract icapsules idose i50 img/kgBB iand ipapaya iextract icapsules idose i100 img/kgBB, icombination iof ikecombrang iextract icapsules idose i50 img/kgBB iand ipapaya iextract icapsules idose i200 img/kgBB, icombination iof ikecombrang iextract icapsules idose i100 img/kgBB iand ipapaya iextract icapsules idose i100 img/kgBB, iand icombination iof ikecombrang iextract icapsules idose i100 img/kgBB iand ipapaya iextract icapsules idose i200 img/kgBB. iData iwere istatistically ianalyzed iusing iOne iWay iAnova. iThe iresults iof idata ianalysis iof iall itreatment igroups ihave ian ieffect ion ireducing iblood isugar ilevels ibecause ithe isig ivalue i<0.05 iexcept ithe inegative icontrol igroup. iBased ion iOne iWay iAnova ianalysis iof ithe ieight imost ieffective itreatments iis ithe icontrol igroup iwith iglibenclamide iadministration, then followed by the combination group of kecombrang leaf extract capsules at a dose of 100mg / kgBB and papaya leaf extract 200mg / kgBB.